Critical issues in education : dialogues and dialectics - Nelson, Jack L.; Palonsky, Stuart; McCarthy, Mary Rose (New York : McGraw Hill, 2013)
There is a great need for critical thinking in schools and by teachers. Current educational reform efforts emphasize student testing on basic information and rote memorization.
Whose interests should school serve? : justice and equity -- What should be taught? : knowledge and literacy -- The School community individual and environments
Includes bibliographical references and index.
Keywords: CRITICAL THINKING